Method for producing adhesive sheet and method for producing optical film with adhesive sheet

By performing surface modification of active energy rays on the adhesive sheet, the odor problem caused by excessive amount of residual cells in the cured adhesive sheet is solved, and the anchoring force of the adhesive sheet is maintained, achieving the dual effect of reducing the residual cells and maintaining the anchoring force.

CN119585387APending Publication Date: 2025-03-07NITTO DENKO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380055799.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-21
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The amount of residual cells in the cured adhesive sheet is too large, resulting in odor problems. At the same time, when the amount of residual cells is reduced by controlling the curing conditions, the anchoring force of the adhesive sheet will be reduced.

Method used

By performing surface modification of active energy rays on the adhesive sheet containing the polymer and the residual monomer, the amount of residual monomer is reduced while reducing the anchoring force is suppressed.

Benefits of technology

The effect of reducing the amount of residual cells in the adhesive sheet is achieved, while maintaining the anchoring force of the adhesive sheet, avoiding the occurrence of odor problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585387A_ABST
    Figure CN119585387A_ABST
Patent Text Reader

Abstract

A method for producing an adhesive sheet according to the present invention comprises performing a surface modification treatment using an active energy ray on a first adhesive sheet containing a polymer of a monomer and a remaining monomer, thereby obtaining a second adhesive sheet in which the amount of the remaining monomer is reduced compared to the first adhesive sheet. The surface modification treatment is, for example, at least one selected from the group consisting of corona treatment, plasma treatment, excimer UV light treatment, and flame treatment. This manufacturing method is suitable for manufacturing an adhesive sheet in which the amount of residual monomers is reduced and the decrease in anchoring force is suppressed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a pressure-sensitive adhesive sheet and a method for producing an optical film with a pressure-sensitive adhesive sheet. Background Art

[0002] Various image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices generally have an optical laminate including an optical film such as a polarizing film and an adhesive sheet. Adhesive sheets are usually used for the bonding between the optical films contained in the optical laminate and the bonding between the optical laminate and the image display panel. As an adhesive sheet, a typical sheet is obtained by curing a monomer group including an acrylic monomer, a silicone monomer, etc. by polymerization and crosslinking. Patent document 1 discloses a method (photocuring method) of forming an adhesive sheet by irradiating a coating layer containing a photocurable composition with light. In addition, patent document 1 discloses a method of reducing the amount of monomers remaining in the formed adhesive sheet by heating and drying.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 4822034 Summary of the invention

[0006] Problems to be solved by the invention

[0007] If the amount of residual monomers contained in the cured adhesive sheet increases, the problem of odor (monomer odor) may arise. For example, the amount of residual monomers may be reduced by controlling the curing conditions. However, according to the research of the present inventors, when the amount of residual monomers is reduced only by controlling the curing conditions, the anchoring force of the adhesive sheet relative to the bonding object may be reduced.

[0008] An object of the present invention is to provide a technique suitable for producing a PSA sheet in which the amount of residual monomers is reduced and a decrease in anchoring force is suppressed.

[0009] Solutions to the problem

[0010] The present invention provides a method for manufacturing an adhesive sheet, the method comprising:

[0011] By subjecting the first PSA sheet including the polymer of the monomer and the residual monomer to a surface modification treatment using active energy rays, a second PSA sheet having a reduced amount of the residual monomer as compared to the first PSA sheet is obtained.

[0012] In another aspect, the present invention provides a method for manufacturing an optical film with an adhesive sheet, the method comprising:

[0013] An optical film is disposed on the surface of the second pressure-sensitive adhesive sheet formed by the method for producing a pressure-sensitive adhesive sheet of the present invention to form an optical film with a pressure-sensitive adhesive sheet.

[0014] Effects of the Invention

[0015] According to the present invention, it is possible to provide a technique suitable for producing a PSA sheet in which the amount of residual monomers is reduced and a decrease in anchoring force is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.

[0017] Figure 2 This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.

[0018] Figure 3A This is a schematic diagram for explaining an example of a method for forming the first pressure-sensitive adhesive sheet.

[0019] Figure 3B This is a schematic diagram for explaining an example of a method for forming the first pressure-sensitive adhesive sheet.

[0020] Figure 3C This is a schematic diagram for explaining an example of a method for forming the first pressure-sensitive adhesive sheet.

[0021] Figure 4 This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.

[0022] Figure 5 This is a schematic diagram for explaining an example of the method for producing the optical film with a pressure-sensitive adhesive sheet of the present invention.

[0023] Figure 6 This is a schematic diagram for explaining an example of the method for producing the optical film with a pressure-sensitive adhesive sheet of the present invention.

[0024] Figure 7 This is a schematic diagram for explaining an example of the method for producing the optical film with a pressure-sensitive adhesive sheet of the present invention. DETAILED DESCRIPTION

[0025] The method for producing a pressure-sensitive adhesive sheet according to the first aspect of the present invention includes:

[0026] By subjecting the first PSA sheet including the polymer of the monomer and the residual monomer to a surface modification treatment using active energy rays, a second PSA sheet having a reduced amount of the residual monomer as compared to the first PSA sheet is obtained.

[0027] In a second aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to the first aspect, the amount of the residual monomer in the second pressure-sensitive adhesive sheet is 5000 ppm (weight basis) or less.

[0028] In a third aspect of the present invention, for example, in the method for producing a PSA sheet according to the first or second aspect, the amount of the residual monomer in the first PSA sheet is 6000 ppm (weight basis) or more.

[0029] In a fourth aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to any one of the first to third aspects, the surface modification treatment is at least one selected from corona treatment, plasma treatment, excimer UV light treatment, and flame treatment.

[0030] In a fifth aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to any one of the first to fourth aspects, the surface modification treatment is performed in an atmosphere having an oxygen concentration of 20% by volume or less.

[0031] In a sixth aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to the fifth aspect, the atmosphere is an inert gas atmosphere.

[0032] In a seventh aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to any one of the first to sixth aspects, the surface modification treatment is performed on the exposed surface of the first pressure-sensitive adhesive sheet.

[0033] In an eighth aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to any one of the first to seventh aspects, the first pressure-sensitive adhesive sheet is a pressure-sensitive adhesive sheet formed from a photocurable composition containing a monomer group and / or a partial polymer of the monomer group.

[0034] In a ninth aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to the eighth aspect, the monomer group includes a (meth)acrylic monomer.

[0035] In the tenth aspect of the present invention, for example, in the method for producing an adhesive sheet of any one of the first to ninth aspects, the method further comprises: irradiating light onto a coating layer of a photocurable composition containing a monomer group and / or a partial polymer of the monomer group to form the first adhesive sheet.

[0036] In the eleventh aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to the tenth aspect, the first pressure-sensitive adhesive sheet is formed by irradiating a laminate including a substrate sheet, the coating layer, and a release liner in this order with the light.

[0037] In a twelfth aspect of the present invention, for example, in the method for producing a pressure-sensitive adhesive sheet according to the tenth or eleventh aspect, the light is different from the active energy ray.

[0038] The method for producing an optical film with a pressure-sensitive adhesive sheet according to a thirteenth aspect of the present invention includes:

[0039] An optical film is disposed on the surface of the second pressure-sensitive adhesive sheet formed by the production method of any one of the first to twelfth aspects to form an optical film with a pressure-sensitive adhesive sheet.

[0040] In a fourteenth aspect of the present invention, for example, in the method for producing an optical film with a pressure-sensitive adhesive sheet according to the thirteenth aspect, the surface is a surface subjected to the surface modification treatment.

[0041] In a fifteenth aspect of the present invention, for example, in the method for producing an optical film with a pressure-sensitive adhesive sheet according to the thirteenth or fourteenth aspect, the optical film includes at least one film selected from a polarizing film and a retardation film.

[0042] In the 16th aspect of the present invention, for example, in the method for producing an optical film with an adhesive sheet of any one of the 13th to 15th aspects, the optical film with an adhesive sheet is formed such that the anchoring force of the second adhesive sheet to the optical film is 12 N / 25 mm or more.

[0043] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with arbitrary modifications within the scope not departing from the gist of the present invention.

[0044] The inventors of the present invention have found a way to reduce the amount of residual monomers by subjecting the adhesive sheet to a surface modification treatment using active energy rays, and have completed the present invention by conducting research based on this idea. The surface modification treatment using active energy rays can reduce the amount of residual monomers contained in the adhesive sheet while suppressing the reduction in anchoring force.

[0045] [Method for producing adhesive sheet]

[0046] Reference Figure 1An example of a method for manufacturing an adhesive sheet of the present invention is described. In this example, a second adhesive sheet 2 is formed by subjecting a first adhesive sheet 1 to a surface modification treatment using an active energy ray 21. The first adhesive sheet 1 contains a polymer of a monomer and residual monomers. Typically, the residual monomers are unreacted monomers in a polymerization reaction that forms a polymer. Compared to the first adhesive sheet 1, the amount of residual monomers in the second adhesive sheet 2 is reduced. The surface modification treatment is applied to a surface 12 of the first adhesive sheet 1 as an exposed surface. More specifically, the surface modification treatment is applied by irradiating the surface 12 with an active energy ray 21. However, as long as the active energy ray 21 is used, the method of the surface modification treatment is not limited to this example. In addition, the surface modification treatment is applied to a surface 12 of the first adhesive sheet 1. However, the surface modification treatment can also be applied to two surfaces 12 and 13 of the first adhesive sheet 1. The surface 12 to which the surface modification treatment is applied becomes a modified surface 14.

[0047] Reference Figure 2 Another example of the method for manufacturing the adhesive sheet of the present invention is described. In this example, the surface modification treatment using active energy rays 21 is performed on the long-shaped first adhesive sheet 1 to form the long-shaped second adhesive sheet 2. The surface modification treatment is performed when the first adhesive sheet 1 passes through the processing device 22. In addition, the surface modification treatment is performed while the first adhesive sheet 1 and the second adhesive sheet 2 are transported in a state of being stacked on the long-shaped substrate sheet 11. Figure 2 The method is particularly suitable for mass production of the second adhesive sheet 2.

[0048] The amount of residual monomers in the second adhesive sheet 2 may be 5000 ppm or less, or 4500 ppm or less, 4000 ppm or less, 3500 ppm or less, 3000 ppm or less, 2500 ppm or less, 2000 ppm or less, 1500 ppm or less, or even 1000 ppm or less. The lower limit of the amount of residual monomers is, for example, 30 ppm or more. In this specification, "ppm" is all based on weight.

[0049] The amount of residual monomers in the first adhesive sheet 1 is, for example, 6000 ppm or more, 8000 ppm or more, 10000 ppm or more, 13000 ppm or more, 15000 ppm or more, 18000 ppm or more, 20000 ppm or more, 25000 ppm or more, 30000 ppm or more, 35000 ppm or more, and further 40000 ppm or more. The upper limit of the amount of residual monomers is, for example, 50000 ppm or less.

[0050] The amount of residual monomers in the first adhesive sheet 1 and the second adhesive sheet 2 can be evaluated by gas chromatography (GC) analysis.

[0051] The surface modification treatment is, for example, at least one selected from corona treatment, plasma treatment, excimer UV light treatment, and flame treatment, and may be corona treatment and / or plasma treatment, or may be corona treatment. In other words, the active energy ray 21 may be at least one selected from electron beam, ion beam, plasma beam, and ultraviolet light. Each surface modification treatment may be implemented by a corresponding known treatment device 22.

[0052] The surface modification treatment can be implemented in an atmospheric atmosphere, but it can also be implemented in an atmosphere with a reduced oxygen concentration compared to the atmosphere (oxygen concentration 20.9 volume %). The surface modification treatment in an atmosphere with a reduced oxygen concentration is particularly suitable for reducing the amount of residual monomers while suppressing the degree of treatment. The surface modification treatment can be implemented in an atmosphere with an oxygen concentration of less than 20 volume %, less than 15 volume %, less than 10 volume %, less than 8 volume %, less than 6 volume %, less than 5 volume %, less than 3 volume %, less than 1 volume %, less than 0.5 volume %, and further can be implemented in an atmosphere with an oxygen concentration of less than 0.3 volume %. The lower limit of the oxygen concentration can be more than 0.01 volume %, more than 0.1 volume %, and further can be more than 0.5 volume %. An example of an atmosphere with a reduced oxygen concentration is a mixed atmosphere of oxygen and an inert gas. Examples of inert gases are argon and nitrogen. However, the inert gas is not limited to the above examples. By surface modification treatment, the anchoring force of the modified surface 14 of the second adhesive sheet 2 can be improved compared to before treatment. Surface modification treatment in an atmosphere with a reduced oxygen concentration is particularly suitable when the treatment degree is increased (for example, the discharge amount is set to 10 kJ / m in the corona treatment). 2 The anchoring force of the modified surface 14 is increased in the above case. The anchoring force is, for example, the anchoring force relative to a resin film such as an optical film. In addition, by implementing the surface modification treatment in an atmosphere with a reduced oxygen concentration according to the type of surface modification treatment, the risk of pyrotechnics can be reduced even when the degree of treatment is increased.

[0053] The surface modification treatment can also be carried out in an atmosphere that is substantially free of oxygen. Substantially free of oxygen means that the oxygen concentration is less than 0.1 volume %, preferably less than 0.05 volume %, and more preferably less than 0.01 volume %. An example of an atmosphere that is substantially free of oxygen is an inert gas atmosphere. In other words, the surface modification treatment can be carried out in an inert gas atmosphere. The surface modification treatment can be carried out under normal pressure (1 atmosphere).

[0054] The conditions of the surface modification treatment as the corona treatment are represented by the discharge amount, for example, 0.6 to 100 kJ / m 2 The lower limit of discharge can be 1kJ / m 2 Above, 2kJ / m 2 Above, 5kJ / m 2 Above, 7kJ / m 2 Above, 10kJ / m2 Above, 13kJ / m 2 Above, 15kJ / m 2 Above, 20kJ / m 2 Above, 25kJ / m 2 Above, 30kJ / m 2 Above, it can be 35kJ / m 2 The upper limit of the discharge amount can be 70 kJ / m 2 Below, 60kJ / m 2 Below, 50kJ / m 2 Below, 45kJ / m 2 Below, 40kJ / m 2 Below, 30kJ / m 2 Below, 20kJ / m 2 Below, and further can be 18kJ / m 2 When the corona treatment is performed in an atmosphere with an oxygen concentration of 10 volume % or more and 20.9 volume % or less, the discharge amount can be 1 to 18 kJ / m 2 When the corona treatment is performed in an atmosphere having an oxygen concentration of 0.01 volume % or more and less than 10 volume %, the discharge amount may be 1 to 60 kJ / m 2 .

[0055] Examples of the base sheet 11 are the same as examples of the base sheet 31 described later that can be used to form the first adhesive sheet 1. The base sheet 31 used to form the first adhesive sheet 1 can be used for the base sheet 11.

[0056] (First adhesive sheet)

[0057] The first adhesive sheet 1 may be an adhesive sheet (photocurable adhesive sheet) formed by a photocurable composition containing a monomer group and / or a partial polymer of the monomer group. However, the first adhesive sheet 1 is not limited to the above examples as long as it contains a polymer of the monomer and residual monomers. The first adhesive sheet 1 may also be an adhesive sheet (thermocurable adhesive sheet) formed by a thermosetting composition containing a monomer group and a solvent. It should be noted that, in terms of the amount of residual monomers contained, there is a tendency to have more in photocurable adhesive sheets than in thermosetting adhesive sheets. This may be due to the fact that oxygen in the atmosphere easily hinders the curing of the photocurable composition, especially near the surface of the sheet. Therefore, in a photocurable adhesive sheet, residual monomers are easily moved to the outside of the adhesive sheet, typically to adjacent layers, causing adverse effects. An example of an adverse effect is the generation of cracks in adjacent optical films. From this point of view, the manufacturing method of the present invention is particularly advantageous when the first adhesive sheet 1 (and the second adhesive sheet 2 formed by the adhesive sheet) is photocurable.

[0058] The photocurable first adhesive sheet 1 can be formed, for example, by irradiating light 35 to a first laminate 34 including a substrate sheet 31, a coating layer 32 containing a photocurable composition, and a release liner 33 in this order. Figure 3A ). By irradiation with light 35, the first adhesive sheet 1 is formed from the coating layer 32 ( Figure 3C The first adhesive sheet 1 formed is sandwiched between the base sheet 31 and the release liner 33 to form a part of the second laminate 36 until the release liner 33 is peeled off. Figure 3A In the example of FIG. 3 , light 35 is irradiated from one side of the substrate sheet 31. Light 35 passes through the substrate sheet 31 and reaches the coating layer 32, thereby curing the coating layer 32. However, it should be noted that irradiation with light 35 may also be implemented from one side of the release liner 33, or from both sides of the release liner 33 and the substrate sheet 31 ( Figure 3B ).

[0059] The manufacturing method of the present invention may further include the above-mentioned step of forming the first adhesive sheet 1. In other words, the manufacturing method of the present invention may further include: forming the first adhesive sheet 1 by irradiating the coating layer 32 containing the photocurable composition containing the monomer group and / or the partial polymer of the monomer group with light 35. In this case, the first laminate 34 containing the substrate sheet 31, the coating layer 32 and the release liner 33 in sequence may be irradiated with light 35 to form the first adhesive sheet 1. The step of forming the first adhesive sheet 1 and the above-mentioned surface modification treatment of the formed first adhesive sheet 1 may be continuously implemented.

[0060] Reference Figure 4 , an example of the manufacturing method of the present invention further including the step of forming the first adhesive sheet 1 is described. In this example, a coating layer 32 of a photocurable composition is formed on one side of a long substrate sheet 31 continuously unrolled from a winding body 41 by a coating device 42. Next, a long release liner 33 continuously unrolled from a winding body 43 is arranged on the coating layer 32 to form a long first laminate 34. Next, the first laminate 34 is irradiated with light 35 from an irradiation device 44 to form a long first adhesive sheet 1. Next, the release liner 33 is peeled off from the second laminate 36 containing the first adhesive sheet 1 and wound up on the winding body 45. The above steps are carried out while conveying the substrate sheet 31 and the release liner 33. Next, the exposed surface (surface 12) of the first adhesive sheet 1 formed by peeling the release liner 33 is subjected to a surface modification treatment using a processing device 22 to form a second adhesive sheet 2 having a modified surface 14. The above steps after peeling off the release liner 33 are performed while conveying the base sheet 31 (11). Figure 4 The method is particularly suitable for mass production of the second adhesive sheet 2.

[0061] <Release liner>

[0062] An example of the base material of the release liner 33 (hereinafter, "base material") is a resin film. Examples of the resin that can be contained in the base material are polyesters such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyether sulfone, polycarbonate, polyamide, polyimide, polyolefin, (meth) acrylic resin, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl alcohol, polyarylate, and polyphenylene sulfide. The resin is preferably a polyester such as polyethylene terephthalate.

[0063] The release liner 33 may have a property of transmitting the light 35 , or may have a property of transmitting the light 35 to the same degree as that of the base sheet 31 .

[0064] The thickness of the release liner 33 is, for example, 10 to 200 μm, or 25 to 150 μm.

[0065] The release liner 33 may also include a layer other than the lining substrate. The release liner 33 may include a release layer. The release liner 33 may include, for example, a lining substrate and a release layer formed on one side of the lining substrate. The release liner 33 may be used in a manner such that the release layer is on the coating layer 32 side.

[0066] Typically, the release layer is a cured layer of a release agent composition containing a release agent. The release agent can use various release agents such as silicone release agents, fluorine release agents, long-chain alkyl release agents, fatty acid amide release agents, and silica powder. The release liner 33 can have a cured layer of a release agent composition containing a silicone release agent as a main component (hereinafter, "silicone release layer"). The silicone release layer is particularly suitable for balancing the adhesion and releasability relative to the first adhesive sheet 1. It should be noted that in this specification, the main component refers to the component with the largest content.

[0067] The silicone release agent includes various curable silicone materials such as addition reaction type, condensation reaction type, ultraviolet curing type, electron beam curing type, solvent-free type, etc., preferably an addition reaction curable silicone material. The addition reaction curable silicone material is particularly suitable for forming a release layer that takes into account both adhesion and peelability relative to the first adhesive sheet 1. The curable silicone material can be a silicone modified resin obtained by introducing reactive silicone into an organic resin such as urethane, epoxy, alkyd resin, etc. by graft polymerization.

[0068] Examples of addition reaction curing silicone materials are polyorganosiloxanes having vinyl or alkenyl groups in the molecule. Addition reaction curing silicone materials may not have hydrosilyl groups. Examples of alkenyl groups are 3-butenyl, 4-pentenyl, 5-hexenyl, 6-heptenyl, 7-octenyl, 8-nonenyl, 9-decenyl, 10-undecenyl and 11-dodecenyl. Examples of polyorganosiloxanes are copolymers of polyalkylalkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane and polymethylethylsiloxane, polyalkylarylsiloxane, and poly(dimethylsiloxane-diethylsiloxane) and other monomers containing Si atoms. Polyorganosiloxane is preferably polydimethylsiloxane.

[0069] A mold release composition containing a silicone-based mold release agent as a main component (hereinafter, "silicone mold release composition") generally contains a crosslinking agent. An example of the crosslinking agent is a polyorganosiloxane having a hydrosilyl group. The crosslinking agent may have two or more hydrosilyl groups in one molecule.

[0070] The silicone release agent composition may also contain a curing catalyst. Examples of the curing catalyst are platinum catalysts. Examples of platinum catalysts are chloroplatinic acid, olefin complexes of platinum, and olefin complexes of chloroplatinic acid. The amount of the platinum catalyst used is, for example, 10 to 1000 ppm (weight basis, converted to platinum) relative to the total solid content of the composition.

[0071] The silicone release agent composition may also contain additives. Examples of additives are release control agents and adhesion improvers. Examples of release control agents are unreactive silicone resins, and more specifically, organosiloxanes such as octamethylcyclotetrasiloxane and MQ resins. The total amount of release control agents and adhesion improvers is, for example, 1 to 30% by weight relative to the total solid content of the composition. Other examples of additives are fillers, antistatic agents, antioxidants, ultraviolet absorbers, plasticizers, and colorants. The total amount of other additives is, for example, 10% by weight or less relative to the total solid content of the composition.

[0072] The silicone release agent composition may also contain an organic solvent. Examples of organic solvents are hydrocarbon solvents such as cyclohexane, n-hexane, and n-heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, and butanol. Two or more organic solvents may also be contained. The amount of organic solvent used is preferably 80 to 99.9% by weight of the silicone release agent composition.

[0073] The release layer can be formed, for example, by heating and drying a coating film containing a release agent composition formed on a lining substrate. The release agent composition can be applied by various coating methods such as roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating. Heating and drying can be performed by hot air drying, for example. The heating temperature and time vary depending on the heat resistance of the lining substrate, and are generally 80 to 150° C. and about 10 seconds to 10 minutes. As required, irradiation with active energy rays such as ultraviolet rays can also be used in combination.

[0074] The thickness of the release layer is, for example, 10 to 300 nm. The upper limit of the thickness may be 200 nm or less, 150 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, less than 100 nm, 90 nm or less, 80 nm or less, 70 nm or less, less than 70 nm, and further may be 65 nm or less. The lower limit of the thickness may be 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, 40 nm or more, 45 nm or more, and further may be 50 nm or more.

[0075] The release liner 33 may be in the form of a single sheet or in the form of a long strip.

[0076] <Base sheet>

[0077] An example of the base sheet 31 is a resin film. Examples of the resin contained in the base sheet 31 are the same as examples of the resin that can be contained in the backing base.

[0078] The base sheet 31 preferably has excellent transmittance of light 35 .

[0079] The thickness of the base sheet 31 is, for example, 10 to 200 μm, or 25 to 150 μm.

[0080] The substrate sheet 31 may be provided with a release layer on the surface of the coating layer 32 side. The examples of the release layer and its preparation method that the substrate sheet 31 may have are the same as the examples of the release layer and its preparation method that the release liner 33 may have. The release layer may be provided on both the release liner 33 and the substrate sheet 31. In this case, the release layers of the two may be formed by a release agent composition containing the same release agent as a main component. In addition, the thickness of the release layers of the two may also be different, for example, the release layer provided by the substrate sheet 31 may be thicker.

[0081] The base sheet 31 can generally be selected to have a greater release force with the first pressure-sensitive adhesive sheet 1 than the release liner 33 .

[0082] The base sheet 31 may be in a single sheet shape or in a long strip shape.

[0083] <Photocurable composition>

[0084] The photocurable composition is a composition that can form the first adhesive sheet 1 from the coating layer 32 by irradiation with light 35. The photocurable composition, for example, contains a monomer group containing a (meth)acrylic monomer and / or a partial polymer of the monomer group. The content of the (meth)acrylic component in the photocurable composition, that is, the (meth)acrylic monomer and its partial polymer, can be 50% by weight or more, 60% by weight or more, 70% by weight or more, and further can be 80% by weight or more. In this case, an acrylic adhesive sheet having a (meth)acrylic polymer and its cross-linked product as the main component can be formed. However, the photocurable composition is not limited to the above examples. In this specification, (meth)acrylic acid refers to acrylic acid and methacrylic acid. (Meth)acrylate refers to acrylate and methacrylate.

[0085] Examples of (meth)acrylic monomers include (meth)acrylic acid alkyl esters having an alkyl group having 1 to 20 carbon atoms in a side chain. The number of carbon atoms in the alkyl group may be 7 or less, 6 or less, 5 or less, or 4 or less. The alkyl group may be linear or branched. Examples of the alkyl (meth)acrylates are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, and octadecyl (meth)acrylate. The alkyl (meth)acrylate may be n-butyl (meth)acrylate.

[0086] The content of the alkyl (meth)acrylate in the monomer group may be, for example, 40% by weight or more, 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or even 95% by weight or more. It should be noted that when calculating the content, the weight of the partial polymer is converted into the weight of each monomer before polymerization.

[0087] The monomer group may include a carboxyl-containing monomer. The carboxyl-containing monomer may be a (meth) acrylic monomer, in other words, the (meth) acrylic monomer may include a carboxyl-containing monomer. Examples of carboxyl-containing monomers are (meth) acrylic acid, (meth) carboxylethyl acrylate, (meth) carboxylpentyl acrylate, itaconic acid, maleic acid, fumaric acid and crotonic acid. The content of the carboxyl-containing monomer in the monomer group may be, for example, less than 10% by weight, less than 9% by weight, less than 8% by weight, less than 7% by weight, less than 6% by weight, less than 5.5% by weight, and further less than 5% by weight. The lower limit of the content may be, for example, more than 0.1% by weight, more than 0.5% by weight, and further more than 1% by weight. The monomer group may also not include a carboxyl-containing monomer.

[0088] The monomer group may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may be a (meth) acrylic acid monomer, in other words, the (meth) acrylic acid monomer may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may contribute to the improvement of the cohesive force of the adhesive sheet. Examples of hydroxyl-containing monomers are 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, 6-hydroxyhexyl (meth) acrylate, 8-hydroxyoctyl (meth) acrylate, 10-hydroxydecyl (meth) acrylate, 12-hydroxylauryl (meth) acrylate, and methyl acrylate (4-hydroxymethylcyclohexyl). The hydroxyl-containing monomer is preferably 2-hydroxyethyl (meth) acrylate and 4-hydroxybutyl (meth) acrylate. The content of the hydroxyl-containing monomer in the monomer group may be, for example, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.8% by weight or less, 0.5% by weight or less, 0.3% by weight or less, 0.2% by weight or less, and further may be 0.1% by weight or less. The lower limit of the content may be, for example, 0.01% by weight or more, 0.03% by weight or more, or further 0.05% by weight or more. The monomer group may not contain a hydroxyl group-containing monomer.

[0089] In the photocurable composition, each of the above monomers may be included in the form of a partial polymer. The partial polymer may be any polymer of a homopolymer and a copolymer. The partial polymer may contribute to the stable formation of the coating layer 32 by appropriately increasing the viscosity of the photocurable composition.

[0090] The photocurable composition generally contains a photopolymerization initiator. Examples of the photopolymerization initiator include a photoradical generator that generates radicals by visible light and / or ultraviolet light having a wavelength shorter than 450 nm.

[0091] Examples of photopolymerization initiators include benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, and benzoin dimethyl ether; substituted benzoin ethers such as anisole methyl ether; substituted acetophenones such as 2,2-diethoxyacetophenone and 2,2-dimethoxy-2-phenylacetophenone; α-hydroxyalkyl phenones such as 1-hydroxycyclohexyl phenyl ketone; substituted α-ol ketones such as 2-methyl-2-hydroxypropiophenone; aromatic sulfonyl chlorides such as 2-naphthalenesulfonyl chloride; photoactive oximes such as 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime; benzophenone, benzoylbenzoic acid, benzoylbenzoic acid, Benzophenone compounds such as methyl benzoate, 4-phenylbenzophenone, hydroxybenzophenone, acryloyl benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, 2,4-diethylthioxanthone; 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6 -bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-piperonyl-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-phenylvinyl-s-triazine, 2-(naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxy-naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl-(piperonyl)-6-triazine, 2,4-trichloromethyl-(4'-methoxyphenylvinyl)-6-triazine, etc. Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], O-(acetyl)-N-(1-phenyl-2-oxo-2-(4'-methoxy-naphthyl)ethylidene)hydroxylamine; phosphine compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; quinone compounds such as 9,10-phenanthrenequinone, camphorquinone, and ethylanthraquinone; borate ester compounds; carbazole compounds; imidazole compounds; and titanocene compounds. The photocurable composition may contain one or more photopolymerization initiators.

[0092] The amount of the photopolymerization initiator in the photocurable composition may be, for example, 0.02 to 10 parts by weight, or 0.05 to 5 parts by weight, relative to 100 parts by weight of the total of the monomer group and the partially polymerized product thereof.

[0093] The photocurable composition may contain a crosslinking agent. An example of a crosslinking agent is a multifunctional monomer having two or more polymerizable functional groups in one molecule. The multifunctional monomer may be a (meth)acrylic monomer. An example of a multifunctional monomer is a monomer having two or more C=C bonds in one molecule, and a monomer having one or more C=C bonds and one or more epoxy groups, aziridine groups, The polyfunctional monomer preferably has two or more C═C bonds in one molecule.

[0094] Examples of the multifunctional monomer include: multifunctional acrylates (ester compounds formed by polyols and (meth)acrylic acid, etc.) such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate (NDDA), 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. The polyfunctional monomer is preferably a polyfunctional acrylate, and more preferably trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, or dipentaerythritol hexa(meth)acrylate.

[0095] The amount of the crosslinking agent varies depending on the molecular weight, the number of functional groups, etc., and is, for example, 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, and further 0.5 parts by weight or less per 100 parts by weight of the total of the monomer group and its partial polymer. The lower limit of the amount of the crosslinking agent is, for example, 0.01 parts by weight or more, and further 0.05 parts by weight or more.

[0096] The photocurable composition may contain additives other than those mentioned above. Examples of the additives include chain transfer agents, silane coupling agents, viscosity modifiers, tackifiers, plasticizers, softeners, antioxidants, fillers, colorants, antioxidants, surfactants, antistatic agents, and ultraviolet absorbers.

[0097] The content of the solvent in the photocurable composition is, for example, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, and further 0.5% by weight or less. The photocurable composition may contain substantially no solvent. Substantially containing no solvent means that a solvent from an additive or the like is allowed to be contained at a content of, for example, 0.1% by weight or less, preferably 0.05% by weight or less, and more preferably 0.01% by weight or less.

[0098] The viscosity of the photocurable composition is preferably 5 to 100 poise. A photocurable composition having a viscosity in the above range is particularly suitable for forming the coating layer 32 .

[0099] <First laminate>

[0100] The first laminate 34 can be formed, for example, by forming a coating layer 32 on a substrate sheet 31 (or a release liner 33) and disposing a release liner 33 (or a substrate sheet 31) on the formed coating layer 32. Alternatively, the first laminate 34 can be formed by coating the photocurable composition so as to flow into a space between the substrate sheet 31 and the release liner 33, which are spaced at a predetermined distance so that their main surfaces face each other.

[0101] The coating layer 32 can be formed by various coating methods such as roll coating, lick roller coating, gravure coating, reverse coating, roller brushing, spray coating, dip roller coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating.

[0102] The thickness of the coating layer 32 can be adjusted according to the target thickness of the second pressure-sensitive adhesive sheet 2 , and may be, for example, 5 to 100 μm, 5 to 50 μm, 5 to 25 μm, or even 5 to 20 μm.

[0103] The first laminate 34 may include another layer in addition to the base sheet 31, the coating layer 32, and the release liner 33. The other layer may be disposed on the side of the base sheet 31 and / or the release liner 33 opposite to the coating layer 32 side. The coating layer 32 is preferably in contact with the base sheet 31 and the release liner 33.

[0104] <Radiation of light>

[0105] The light 35 irradiated to the first stack 34 is, for example, visible light or ultraviolet light having a wavelength shorter than 450 nm. The light 35 may include light of a wavelength in the same region as the absorption wavelength of the photopolymerization initiator contained in the photocurable composition. The light 35 obtained by cutting off short-wavelength light having a wavelength of less than 200 nm, preferably less than 300 nm, through an optical filter or the like may be irradiated, and cutting off the short-wavelength light is suitable for suppressing the degradation of the substrate sheet 31 and / or the release liner 33 caused by the light 35. The light source of the light 35 is, for example, an irradiation device having an ultraviolet irradiation lamp. Examples of ultraviolet irradiation lamps are ultraviolet LEDs, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, microwave-excited mercury lamps, black light lamps, chemical lamps, sterilization lamps, low-pressure discharge mercury lamps, and excimer lasers. Two or more ultraviolet irradiation lamps may also be combined.

[0106] The irradiation of light 35 may be continuous or intermittent.

[0107] The irradiation intensity of the light 35 is, for example, 1 to 20 mW / cm 2 The irradiation time of the light 35 is, for example, 5 minutes to 5 hours. The cumulative light intensity of the light 35 on the first stack 34 is, for example, 100 to 5000 mJ / cm 2 .

[0108] The light 35 may be different from the active energy ray 21. For example, the light 35 may be different from the active energy ray 21 in kind. The active energy ray 21 as light may be different from the light 35 in wavelength. When the active energy ray 21 is ultraviolet light, the wavelength may be 200 nm or less.

[0109] The polymerization rate of the monomer group in the first pressure-sensitive adhesive sheet 1 is preferably 90% or more. The polymerization rate may be 95% or more, 96% or more, 97% or more, or even 98% or more.

[0110] The gel fraction of the first pressure-sensitive adhesive sheet 1 may be, for example, 50% or more, 75% or more, 80% or more, or even 85% or more.

[0111] The peeling force of the release liner 33 with respect to the first pressure-sensitive adhesive sheet 1 may be smaller than the peeling force of the base sheet 31 with respect to the first pressure-sensitive adhesive sheet 1 .

[0112] (Second adhesive sheet)

[0113] The second adhesive sheet 2 may be of a photocurable type.

[0114] The thickness of the second pressure-sensitive adhesive sheet 2 may be, for example, 2 to 70 μm, 2 to 50 μm, 5 to 40 μm, 10 to 30 μm, 10 to 25 μm, or further 10 to 20 μm.

[0115] The gel fraction of the second pressure-sensitive adhesive sheet 2 may be, for example, 50% or more, 75% or more, 80% or more, or even 85% or more.

[0116] The second adhesive sheet 2 can be used, for example, for an optical laminate containing an optical film. In other words, the second adhesive sheet 2 can be an adhesive sheet for an optical laminate. The optical laminate can be an optical film with an adhesive sheet. The second adhesive sheet 2 can be used in a manner that the modified surface 14 becomes the optical film side, or can be used in a manner that is connected to the optical film. However, the purpose and method of use of the second adhesive sheet 2 are not limited to the above examples.

[0117] [Method for producing optical film with pressure-sensitive adhesive sheet]

[0118] Reference Figure 5 An example of a method for manufacturing an optical film with an adhesive sheet of the present invention is described. In this example, an optical film 3 is arranged on the modified surface 14 of the second adhesive sheet 2 arranged on the substrate sheet 11 to form an optical film 51 with an adhesive sheet. The optical film 51 with an adhesive sheet includes the substrate sheet 11, the second adhesive sheet 2 and the optical film 3 in sequence. The optical film 51 with an adhesive sheet can be used in an image display device or the like directly or after the substrate sheet 11 is peeled off, for example, in the form of an optical laminate having the second adhesive sheet 2 and the optical film 3. The optical laminate can be attached to an object (such as an image forming panel) via the second adhesive sheet 2. However, it should be noted that the use of the optical film 51 with an adhesive sheet is not limited to the above example. Another component such as an optical film can also be arranged on the exposed surface 37 formed by peeling the substrate sheet 11 from the optical film 51 with an adhesive sheet. As an example, an optical film 52 with an adhesive sheet that includes an optical film 3A, a second adhesive sheet 2 and an optical film 3B in sequence can be formed (see Figure 6 ). The optical films 3A and 3B may be the same or different from each other.

[0119] The optical film 3 may be directly or indirectly disposed on the modified surface 14 and the exposed surface 37. In other words, the optical film 3 may be disposed in contact with the modified surface 14 or the exposed surface 37, or may be disposed with another layer sandwiched between the modified surface 14 or the exposed surface 37.

[0120] The side of the optical film 3 that contacts the second adhesive sheet 2 may be a surface that has been subjected to surface modification treatment by active energy rays. This method is particularly suitable for improving the anchoring force between the second adhesive sheet 2 and the optical film 3. Examples of surface modification treatment for the optical film 3, including preferred examples, are the same as those for the first adhesive sheet 1.

[0121] Reference Figure 7 Another example of the method for producing the optical film with the adhesive sheet of the present invention is described. Figure 4The modified surface 14 of the second adhesive sheet 2 formed by the method is provided with a long strip of optical film 3, thereby forming a long strip of optical film 51 with adhesive sheet. The optical film 3 is continuously unwound from the roll 46 and provided on the modified surface 14. The above steps are carried out while the substrate sheet 31 (11) is conveyed. Figure 7 As shown, the second adhesive sheet 2 and the optical film with adhesive sheet 51 may be formed continuously. Alternatively, the first adhesive sheet 1, the second adhesive sheet 2, and the optical film with adhesive sheet 51 may be formed continuously. Figure 7 The method is particularly suitable for mass production of the optical film 51 with an adhesive sheet.

[0122] The optical film 3 is, for example, a film including at least one selected from a polarizing film and a phase difference film. The optical film 3 may be a laminated film including a polarizing film and / or a phase difference film. The optical film 3 may include a film made of glass. However, the optical film 3 is not limited to the above examples.

[0123] The polarizing film includes a polarizer. Typically, the polarizing film includes a polarizer and a protective film (transparent protective film). The protective film is, for example, arranged in contact with the main surface (surface with the widest area) of the polarizer. The polarizer can be arranged between two protective films. The protective film can be arranged on at least one side of the polarizer.

[0124] The polarizer is not particularly limited, and examples thereof include: a polarizer obtained by adsorbing a dichroic substance such as iodine and a dichroic dye on a hydrophilic polymer film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, and a partially saponified film of an ethylene-vinyl acetate copolymer, and then uniaxially stretching the film; a polyene oriented film such as a dehydrated product of polyvinyl alcohol and a dehydrochlorinated product of polyvinyl chloride, etc. Typically, the polarizer is formed of a polyvinyl alcohol film (polyvinyl alcohol films include partially saponified films of ethylene-vinyl acetate copolymers) and a dichroic substance such as iodine.

[0125] The thickness of the polarizer is not particularly limited, for example, it is 80 μm or less, it can be 50 μm or less, 30 μm or less, 25 μm or less, and further, it can be 20 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, for example, it is 1 μm or more, it can be 5 μm or more, 10 μm or more, and further, it can be 15 μm or more. The dimensional change of the thin polarizer (for example, the thickness is 20 μm or less) is suppressed, which can contribute to the durability of the optical laminate, especially the durability at high temperature.

[0126] As the material of the protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the protective film can be a thermosetting resin or ultraviolet curing resin such as (meth)acrylic acid, urethane, acrylic urethane, epoxy, silicone, etc. In the case where the polarizing film has two protective films, the materials of the two protective films can be the same or different from each other. For example, a protective film formed of a thermoplastic resin can be bonded to one main surface of the polarizer via an adhesive, and a protective film formed of a thermosetting resin or an ultraviolet curing resin can be bonded to the other main surface of the polarizer. The protective film can contain one or more arbitrary additives. Examples of the additive include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.

[0127] The thickness of the protective film can be appropriately determined, and is generally about 10 to 200 μm from the perspectives of strength, workability such as handling properties, and thin film properties.

[0128] The polarizer and the protective film are usually bonded together via a water-based adhesive or the like. Examples of the water-based adhesive include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex, water-based polyurethane, and water-based polyester. Other adhesives other than the above-mentioned adhesives include ultraviolet curing adhesives and electron beam curing adhesives. Electron beam curing polarizer adhesives show suitable adhesion to various protective films. The adhesive may also contain a metal compound filler.

[0129] In the polarizing film, a retardation film or the like may be formed on the polarizer instead of the protective film. Another protective film or a retardation film or the like may be provided on the protective film.

[0130] The protective film may be provided with a hard coating layer on the surface opposite to the surface bonded to the polarizer, and may be subjected to treatment for the purpose of anti-reflection, anti-blocking, diffusion, anti-glare, etc.

[0131] The polarizing film may be a circular polarizing film.

[0132] As the retardation film, a film obtained by stretching a polymer film or a film obtained by orienting and fixing a liquid crystal material can be used. The retardation film has birefringence in the plane and / or in the thickness direction, for example.

[0133] The phase difference film includes a phase difference film for antireflection (refer to Japanese Patent Application Publication No. 2012-133303

[0221] ,

[0222] , and

[0228] ), a phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303

[0225] and

[0226] ), and a tilted orientation phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303

[0227] ).

[0134] The specific structure of the retardation film, such as the retardation value, the arrangement angle, the three-dimensional birefringence, whether it is a single layer or a multilayer, etc., is not particularly limited, and a known retardation film can be used.

[0135] The thickness of the retardation film is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, particularly preferably 3 to 8 μm.

[0136] The phase difference film may include, for example, a quarter wave plate and / or a half wave plate in which a liquid crystal material is oriented and fixed.

[0137] In the optical films 51 and 52 with adhesive sheets, the anchoring force of the second adhesive sheet 2 relative to the optical film 3 can be 10N / 25mm or more, or 12N / 25mm or more. In other words, the optical films 51 and 52 with adhesive sheets can be formed in which the anchoring force of the second adhesive sheet 2 relative to the optical film 3 is 10N / 25mm or more, and further can be 12N / 25mm or more. The anchoring force can be 13N / 25mm or more, 14N / 25mm or more, 15N / 25mm or more, 16N / 25mm or more, and further can be 17N / 25mm or more. The upper limit of the anchoring force is, for example, 50N / 25mm or less, and can be 30N / 25mm or less. It should be noted that a film containing a (meth) acrylic resin as a main component (hereinafter, "acrylic film") is sometimes used in an optical film 3 such as a protective film of a polarizer. There is a tendency that the bonding strength between the acrylic film and the adhesive sheet is generally small. From this viewpoint, the second pressure-sensitive adhesive sheet 2 having the second anchor force within the above range is particularly suitable for bonding to the optical film 3 which is an acrylic film.

[0138] The anchoring force of the second adhesive sheet 2 relative to the optical film 3 can be measured by the following method. Cut the laminate of the optical film 3 and the second adhesive sheet 2 into a width of 25mm×length of 150mm as a test piece. As long as the optical film 3 and the second adhesive sheet 2 are connected together, the laminate may also include other layers. Next, the entire surface of the optical film 3 possessed by the test piece is superimposed on a stainless steel test plate via a double-sided tape, and a 2kg roller is reciprocated once to press them together. Next, the second adhesive sheet 2 possessed by the test piece is superimposed on the evaluation sheet, and a 2kg roller is reciprocated once to press them together. The evaluation sheet has a size of 30mm in width×150mm in length, and is not particularly limited as long as it will not peel off from the second adhesive sheet 2 during the test. As an evaluation sheet, for example, an ITO film (125Tetoraito OES (manufactured by Oike Industry Co., Ltd.) can be used. Next, using a commercially available tensile testing machine, the second adhesive sheet 2 was peeled off from the optical film 3 at a peeling angle of 180° and a tensile speed of 300 mm / min while holding the evaluation sheet, and the average value of the peeling force at this time was determined as the anchoring force of the second adhesive sheet 2 to the optical film 3. The above test was performed in an atmosphere of 23°C ± 5°C.

[0139] An image display device can be formed using optical films 51 and 52 with adhesive sheets. The image display device can be formed by, for example, bonding optical films 51 and 52 with adhesive sheets to an image display panel. The bonding can be performed using the second adhesive sheet 2. The image display device can be an organic EL display or a liquid crystal display. However, the image display device is not limited to the above examples. The image display device can also be a field luminescence (EL) display, a plasma display (PD), a field emission display (FED: Field Emission Display), etc. The image display device can be used for household appliances, in-vehicle applications, public information displays (PID), etc.

[0140] Example

[0141] Hereinafter, the present invention will be described in more detail by way of examples. However, the present invention is not limited to the examples shown below.

[0142] [Preparation of monomer slurry]

[0143] (Synthesis example 1)

[0144] 99 parts by weight of n-butyl acrylate (BA) and 1 part by weight of 4-hydroxybutyl acrylate (HBA), as well as 0.05 parts by weight of Omnirad184 (1-hydroxycyclohexyl phenyl ketone, manufactured by IGM Resins) and 0.05 parts by weight of Omnirad651 (2,2-dimethoxy-1,2-diphenylethane-1-one, manufactured by IGM Resins) as photopolymerization initiators were placed in a four-necked flask, and irradiated with ultraviolet rays in a nitrogen atmosphere, thereby obtaining a partially photopolymerized monomer syrup A1. Ultraviolet irradiation was performed until the viscosity of the liquid in the flask (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached about 20 Pa·s.

[0145] (Synthesis example 2)

[0146] Monomer syrup A2 was prepared in the same manner as monomer syrup A1 except that the monomers used were changed as shown in Table 1. In addition, "AA" in Table 1 represents acrylic acid.

[0147] [Table 1]

[0148]

[0149] [Preparation of Photocurable Composition]

[0150] The monomer syrup and the crosslinking agent were mixed to obtain photocurable compositions C1 and C2 so as to have the compositions shown in the following Table 2. In addition, "NDDA" in Table 2 is 1,9-nonanediol diacrylate.

[0151] [Table 2]

[0152]

[0153] [Preparation of the first adhesive sheet]

[0154] (Manufacturing Example 1: Preparation of Release Liner A)

[0155] 30 parts by weight of addition reaction curing silicone (LTC761 containing hexenyl polysiloxane, 30% by weight toluene solution, manufactured by Dow Corning Toray), 0.9 parts by weight of release control agent (BY24-856 containing unreacted silicone resin, manufactured by Dow Corning Toray), 2 parts by weight of curing catalyst (SRX212 containing platinum catalyst, manufactured by Dow Corning Toray), and a toluene / hexane mixed solvent (volume ratio 1:1) as a diluent were mixed to obtain a silicone release agent composition. The concentration of silicone solid content in the release agent composition was 1.0% by weight. Next, the release agent composition was applied to one side of a liner substrate (Lumirror XD500P as a polyester film, thickness 75 μm) by a wire bar, and heated at 130°C for 1 minute to prepare a release liner A having a release layer (thickness 60 nm) on one side.

[0156] (Manufacturing Example 2: Preparation of Release Liner B)

[0157] A release liner B having a release layer (thickness 120 nm) on one surface was prepared in the same manner as in Production Example 1 except that the coating thickness of the release agent composition on the lining substrate was changed.

[0158] (Manufacturing Example 3: Preparation of the First PSA Sheet A)

[0159] The photocurable composition C1 was applied by an applicator in a manner sandwiched between the release liner A prepared in Production Example 1 and the release liner B prepared in Production Example 2, thereby obtaining a first laminate consisting of the release liner A, the coating layer, and the release liner B. Both the release liners A and B were used so that the release layer and the coating layer were in contact. Next, the irradiation intensity was 2.5 mW / cm 2 The coating layer was photocured by irradiating the release liner A side of the first laminate with ultraviolet light (black light source) under the conditions of irradiation time of 640 seconds, thereby forming a second laminate consisting of release liner A, first adhesive sheet A (thickness 20 μm) and release liner B. The polymerization rate in the first adhesive sheet A formed was 98.1%. The amount of residual monomers in the first adhesive sheet A formed was 18230 ppm. The amount of residual monomers was evaluated by GC analysis. The amount of residual monomers in the following first adhesive sheet and second adhesive sheet was also evaluated in the same manner. The device and measurement conditions for GC analysis are shown below.

[0160] · Device used: GC7890A (manufactured by Agilent Technologies)

[0161] Column: HP-1 (manufactured by Agilent Technologies)

[0162] Detector: Flame ionization detector (FID)

[0163] Inlet temperature: 250℃

[0164] · Measurement temperature conditions: The following (1) to (4) were followed in order: (1) maintained at 0°C for 3 minutes, (2) the temperature was raised at a rate of 10°C / min, (3) the temperature was raised at a rate of 20°C / min after reaching 120°C, and (4) maintained at 300°C for 3 minutes.

[0165] Sample preparation method: 0.05 g of the sample (adhesive sheet) was collected in a screw-cap bottle, 2.5 mL of ethyl acetate was added, and the mixture was shaken overnight. The resulting solution was filtered through a 0.45 μm membrane filter, and 1 μL of the filtrate was injected into the GC for analysis.

[0166] (Manufacturing Example 4: Preparation of the First PSA Sheet B)

[0167] A second laminate consisting of a release liner A, a first adhesive sheet B (thickness 20 μm), and a release liner B was formed in the same manner as in Manufacturing Example 2, except that the photocurable composition C2 was used instead of the photocurable composition C1 and the ultraviolet irradiation time was changed to 480 seconds. The polymerization rate of the formed first adhesive sheet B was 97.9%. In addition, the amount of residual monomers in the first adhesive sheet B was 19320 ppm.

[0168] (Manufacturing Example 5: Preparation of the First PSA Sheet C)

[0169] A second laminate consisting of release liner A, first adhesive sheet C (thickness 20 μm), and release liner B was formed in the same manner as in Production Example 2 except that the ultraviolet irradiation time was changed to 2000 seconds. The polymerization rate of the formed first adhesive sheet C was 97.7%. The amount of residual monomers in the first adhesive sheet C was 1500 ppm.

[0170] [Preparation of the Second Adhesive Sheet]

[0171] (Example 1)

[0172] The release liner B was peeled off from the second laminate prepared in Production Example 3 to expose one side of the first adhesive sheet A. Next, the film was discharged at a discharge amount of 14.6 kJ / m in an atmosphere having an oxygen concentration of 0.1 vol% (oxygen-nitrogen mixed atmosphere, 1 atm). 2 The exposed surface of the first adhesive sheet A was subjected to corona treatment to obtain a second adhesive sheet. The amount of residual monomers in the obtained second adhesive sheet was 2990 ppm.

[0173] (Examples 2 to 9)

[0174] The second adhesive sheets of Examples 2 to 9 were obtained in the same manner as in Example 1 except that the first adhesive sheet shown in Table 3 below was subjected to corona treatment under the conditions shown in Table 3. It should be noted that the treatment atmospheres with oxygen concentrations of 1.0 volume %, 0.1 volume % and 0.01 volume % were set as an oxygen-nitrogen mixed atmosphere. The treatment atmosphere with an oxygen concentration of 20.9 volume % was set as an atmospheric atmosphere. It should be noted that the pressure of the treatment atmosphere was all 1 atmosphere.

[0175] (Comparative Example 1)

[0176] The first PSA sheet A obtained by peeling the release liner B from the second laminate prepared in Production Example 2 was used as the PSA sheet a of Comparative Example 1 without being subjected to corona treatment.

[0177] (Comparative Example 2)

[0178] The first PSA sheet C obtained by peeling off the release liner B from the second laminate prepared in Production Example 4 was used as the PSA sheet b of Comparative Example 2 without being subjected to corona treatment.

[0179] (Comparative Example 3)

[0180] The first PSA sheet B obtained by peeling the release liner B from the second laminate prepared in Production Example 3 was used as PSA sheet c of Comparative Example 3 without being subjected to corona treatment.

[0181] [Table 3]

[0182]

[0183] ※ The second PSA sheets in Comparative Examples 1 to 3 are PSA sheets a to c, respectively.

[0184] [Anchoring force]

[0185] Polarizing film D1 was arranged on the corona-treated surface of the second adhesive sheet prepared in the example and on the exposed surfaces of adhesive sheets a to c of the comparative example to prepare an optical laminate. The polarizing film D1 was arranged in such a way that the surface on the transparent protective film side formed by the modified methacrylic resin was in contact with the adhesive sheet. Next, for the produced optical laminate, the anchoring force between the adhesive sheet and the polarizing film was measured by the above method. The double-sided tape used was the trade name "No.531" manufactured by Nitto Denko Corporation. A SUS304 plate (width 40 mm × length 120 mm) was used as the stainless steel test plate. An ITO film (125 Tetoraito OES, manufactured by Oike Industries) was used as the evaluation sheet. Autograph SHIMAZU AG-I10KN (manufactured by Shimadzu Corporation) was used as the tensile testing machine.

[0186] A polarizing film D1 for anchoring force evaluation was prepared as follows. A polyvinyl alcohol film of 80 μm in thickness was stretched to 3 times while being dyed in an iodine solution of 0.3% at 30°C for 1 minute between rollers of different speed ratios. Next, it was immersed in an aqueous solution of 4% boric acid and 10% potassium iodide at 60°C for 0.5 minutes, and stretched to a total stretch ratio of 6 times. Next, it was immersed in an aqueous solution of 1.5% potassium iodide at 30°C for 10 seconds for washing, and then dried at 50°C for 4 minutes, thereby obtaining a polarizer of 28 μm in thickness. A transparent protective film of 30 μm in thickness formed of a modified acrylic polymer having a lactone ring structure was bonded to one side of the polarizer via a polyvinyl alcohol-based adhesive. Furthermore, a transparent protective film having a thickness of 47 μm and a hard coating layer (HC) formed on a triacetyl cellulose film (manufactured by Konica Minolta, trade name "KC4UY") was attached to the other side of the polarizer via a polyvinyl alcohol-based adhesive. The film was heated and dried in an oven set at 70°C for 5 minutes to produce a polarizing film D2. Furthermore, the film was discharged in an atmosphere at a discharge amount of 63 W / (m 2 (a) The surface of the polarizing film D2 on the transparent protective film side formed of a modified acrylic polymer was subjected to a corona treatment.

[0187] [Stink]

[0188] The odor of the second PSA sheet produced in the example and each PSA sheet of the comparative example was evaluated as follows.

[0189] The adhesive sheet of the evaluation object is 4 cm 2 An aluminum cup was placed and heated at 40°C for 10 minutes under a nitrogen flow using a heating device (MARKES, T-CTE250). All gases generated by heating were captured by passing through the adsorbent. The adsorbent after capturing the gas was heated by a heating desorption device (MARKES, TD-100) directly connected to the GC / MS device to release the captured components. The free components were introduced into the column of GC / MS, and a sensory test (olfactory GC / MS test) was carried out by a panel of three people to determine whether the gas separated by the column was smelled or not. The case where the panel of three people was judged to feel the odor was set as C, the case of two people was set as B, the case of one person was set as A, and the case of zero people was set as AA. In addition, the retention time of the odor reaching the peak when the odor was felt was determined by the panel of experts, and the component that brought about the peak was determined by GC / MS analysis. The component that brought about the peak was n-butyl acrylate (BA) in all adhesive sheets whose odor was evaluated as A, B or C.

[0190] [Productivity]

[0191] The productivity of the second PSA sheet produced in the example and each PSA sheet of the comparative example was evaluated as follows.

[0192] A: A case where the time T required for the amount of residual monomers to reach 10000 ppm or less is 480 seconds or less is defined as A.

[0193] B: The case where the time T required for the residual monomer amount to reach 10000 ppm or less is more than 480 seconds and is 960 seconds or less is defined as B.

[0194] C: The case where the time T required for the residual monomer amount to reach 10000 ppm or less exceeds 960 seconds, or the case where the residual monomer amount exceeds 10000 ppm is defined as C.

[0195] It should be noted that the time T, for the second adhesive sheet obtained by corona treatment, is the treatment time required for the residual monomer amount to be reduced to 10,000 ppm or less by the treatment, and for the adhesive sheet of Comparative Example 2 obtained without corona treatment, is the ultraviolet irradiation time required for the residual monomer amount to be reduced to 10,000 ppm or less when the second laminate is formed from the first laminate.

[0196] The evaluation results are shown in Table 4 below together with the conditions of the corona treatment and the amount of residual monomers in the second PSA sheet.

[0197] [Table 4]

[0198]

[0199] ※ The second PSA sheets in Comparative Examples 1 to 3 are PSA sheets a to c, respectively.

[0200] Industrial Applicability

[0201] The pressure-sensitive adhesive sheet obtained by the production method of the present invention can be used for, for example, an optical layered body or an image display device.

Claims

1. A method for manufacturing an adhesive sheet, the method comprising: By subjecting the first PSA sheet including the polymer of the monomer and the residual monomer to a surface modification treatment using active energy rays, a second PSA sheet having a reduced amount of the residual monomer as compared to the first PSA sheet is obtained.

2. The method for producing a pressure-sensitive adhesive sheet according to claim 1, wherein: The amount of the residual monomer in the second pressure-sensitive adhesive sheet is 5000 ppm (weight basis) or less.

3. The method for producing a pressure-sensitive adhesive sheet according to claim 1, wherein: The amount of the residual monomer in the first pressure-sensitive adhesive sheet is 6000 ppm (weight basis) or more.

4. The method for producing a pressure-sensitive adhesive sheet according to claim 1, wherein: The surface modification treatment is at least one selected from corona treatment, plasma treatment, excimer UV light treatment and flame treatment.

5. The method for producing a pressure-sensitive adhesive sheet according to claim 1, wherein: The surface modification treatment is performed in an atmosphere having an oxygen concentration of 20% by volume or less.

6. The method for producing a pressure-sensitive adhesive sheet according to claim 5, wherein: The atmosphere is an inert gas atmosphere.

7. The method for producing a pressure-sensitive adhesive sheet according to claim 1, wherein: The surface modification treatment is performed on the exposed surface of the first adhesive sheet.

8. The method for producing a pressure-sensitive adhesive sheet according to claim 1, wherein: The first adhesive sheet is an adhesive sheet formed from a photocurable composition containing a monomer group and / or a partial polymer of the monomer group.

9. The method for producing a pressure-sensitive adhesive sheet according to claim 8, wherein: The monomer group includes a (meth)acrylic monomer.

10. The method for producing an adhesive sheet according to claim 1, further comprising: The first adhesive sheet is formed by irradiating a coating layer made of a photocurable composition containing a monomer group and / or a partial polymer of the monomer group with light.

11. The method for producing a pressure-sensitive adhesive sheet according to claim 10, wherein: The first pressure-sensitive adhesive sheet is formed by irradiating a laminate including a substrate sheet, the coating layer, and a release liner in this order with the light.

12. The method for producing a pressure-sensitive adhesive sheet according to claim 10, wherein: The light is different from the active energy ray.

13. A method for manufacturing an optical film with an adhesive sheet, the method comprising: An optical film is disposed on the surface of the second pressure-sensitive adhesive sheet formed by the production method according to any one of claims 1 to 12 to form an optical film with a pressure-sensitive adhesive sheet.

14. The method for producing an optical film with a pressure-sensitive adhesive sheet according to claim 13, wherein: The surface is a surface subjected to the surface modification treatment.

15. The method for producing an optical film with a pressure-sensitive adhesive sheet according to claim 13, wherein: The optical film includes at least one film selected from a polarizing film and a phase difference film.

16. The method for producing an optical film with a pressure-sensitive adhesive sheet according to claim 13, wherein: The optical film with an adhesive sheet is formed such that the anchoring force of the second adhesive sheet to the optical film is 12 N / 25 mm or more.

Citation Information

Patent Citations

  • JP1973022034B1

  • Optical display device having polarizing film

    JP2012133303A